Cap Go Meh Cultural Tourism as an Effort to Maintain Socio-Cultural Resistance in the Singkawang City - Lio Kurniawan; Arthur Josias Simon Runturambi; Thomas Sunaryo; Nova Wijaya (International Journal of Multi Discipline Science (IJ-MDS), 2023)
The purpose of this research was to find out how the Singkawang Cap Go Meh Festival can survive for a long time and what is the role of socio-cultural actors in maintaining Cap Go Meh as a strategy for maintaining social resilience. To achieve this goal, it was determined that the object of research was the Cap Go Meh Cultural Festival while the subject of the research was the figures who play a role in the success of the Cap Go Meh festival and how their respective roles create social and cultural resilience such as the Government and Legislative Parliament of the Singkawang-City, the Head of the Education Office and Culture, Head of Tourism, Youth and Sports Service, Head of the Malay Cultural Customary Council (MABM), Head of the Chinese Cultural Customary Council (MABT), Head of the Dayak Traditional Council (DAD), Head of the Javanese Association, and Cap Go Meh Committee. This study used data collection techniques through observation, interviews, and documentation and data analysis techniques were inductive. The results of this study could be concluded that the Singkawang Cap Go Meh Festival was unique because the Singkawang Cap Goh Mes Cultural Festival involved all ethnicities in Singkawang City, the Chinese ethnic community really defended its culture, the Singkawang Cap Go Meh Festival was proven to be leading tourism because it brings in many foreign tourists, the Singkawang Cap Go Meh Festival was a driving factor for creating socio-cultural resilience. This could be proven by Singkawang City being one of the number one tolerant Cities in Indonesia.